Relationship Between the Supervisory Approach and the Satisfaction of the University Theses in Dentistry - Castro-Rodríguez, Yuri (Odovtos - International Journal of Dental Sciences, 2021)
The objective of this study was to relate the degree of satisfaction that graduates had with the supervisory approach during the development of the undergraduate thesis. A cross-sectional study, including 102 graduate students from the Faculty of Dentistry of the Universidad Nacional Mayor de San Marcos. Lima. Peru. The survey technique was used to collect information on the satisfaction of the thesis supervision (valued on a score from 1 to 6, where higher scores showed greater satisfaction) and the supervisor’s approach. Results showed that 59% of supervisors had a collaborative approach, 29.6% a non-directive approach. Collaborative supervisors obtained a higher satisfaction score (5.2±0.7) while the directive approach obtained the lowest score (3.3±0.5) (p<0.05). Women presented a higher satisfaction score (5.4±0.2 vs 4.8±0.4) (p<0.05). There is a relationship between the collaborative supervision style and greater student satisfaction during the thesis process. Students indicated being less satisfied with the managerial supervision style of the thesis.